Microbial quality of well water from rural and urban households in Karnataka, India: A cross-sectional study - Chiranjay Mukhopadhyay; Shashidhar Vishwanath; Vandana K. Eshwara; Shamanth A. Shankaranarayana; Afrin Sagir (Elsevier, 2012)
Summary: Objective: The objective of this study was to evaluate the microbial quality of the well water used as a drinking source in urban and rural households. Methods: A total of 80 household well water samples were analyzed by the multiple fermentation tube method to determine the presumptive coliform count/most probable number of coliforms, and the isolates were identified using standard procedures, followed by susceptibility testing. Results: Fecal indicator organisms, including Escherichia coli and Enterococcus spp. were isolated from 22 (27.5%) samples, and the majority (92.5%) of the water sources were contaminated with coliforms. A total of 170 bacterial isolates were obtained, including coliforms (70%), Enterococcus spp. (1.8%) and saprophytes (28.2%). A significant number of isolates were multi-drug resistant, which is a cause of concern. A comparison of the microbial quality of the water between urban and rural households revealed no significant differences. Conclusion: It might be prudent to monitor the bacteriological quality of well water at the source in addition to resistance profiles of the isolates. Keywords: Escherichia coli, Fecal coliforms, Most probable number, Total coliforms, Water quality